Vertically Integrated Dual-porosity and Dual-permeability Models for CO2 Sequestration in Fractured Geological Formation. (July 2017) - Guo, Bo; Tao, Yiheng; Bandilla, Karl; Celia, Michael
Abstract: Analysis of geological storage of carbon dioxide (CO2 ) in deep saline aquifers requires computationally efficient mathematical models to predict the pressure evolution and the injected CO2 plume migration. The subsurface system of CO2 injection into saline aquifers can be modeled as a two-phase flow system, with a non-wetting less dense (supercritical) CO2 phase and a denser brine as the wetting phase. For unfractured geological formations, one type of simplified model can be developed by integrating the three-dimensional governing equations in the vertical dimension. The vertically integrated models that assume buoyant segregation and vertical pressure equilibrium are referred to as vertical equilibrium (VE) models. VE models are computationally efficient owing to the dimension reduction from vertical integration, and have been extensively applied to field-scale modeling of CO2 injection, migration, and leakage in the past decade. For fractured geological formations, it is challenging to directly use vertically integrated models, because CO2 migration in fractured formations involves two different characteristic time scales due to significant contrast of permeability between the fractures and matrix. The high permeability of the fractures leads to fast buoyant segregation of CO2 and brine in the vertical direction within the fractures, while lower permeability of the matrix typically leads to much slower flow dynamics that involve longer time scales for segregation. In this paper, we use a dual-continuum approach to conceptualize the fractured geological formation, treating the fractures and the rock matrix blocks as overlapping continua, and develop vertically integrated models for CO2 injection in fractured geological formation. We use a VE model for the fracture domain and explore different model options for the matrix domain, including the classical dual-porosity model that treats the matrix as a source/sink term for the fracture as well as other more advanced models that explicitly account for the two-phase flow dynamics of the CO2 and brine in the matrix domain. We present the modeling framework and show preliminary model comparison results to demonstrate the applicability of the new models.